Longitudinal evaluation of manufacturer-specific differences for high-sensitive CRP EQA results - Weiss, Nathalie; Vierbaum, Laura; Kremser, Marcel; Kaufmann-Stoeck, Anne; Kappler, Silke; Ballert, Silvia; Kabrodt, Kathrin; Hunfeld, Klaus-Peter; Schellenberg, Ingo (Frontiers in Molecular Biosciences, 2024)
Background: C-reactive protein (CRP) is an established serum biomarker for different pathologies such as tissue injury and inflammatory events. One rising area of interest is the incorporation of low concentrations of CRP, so called high-sensitive (hs-) CRP, in the risk assessment and treatment monitoring of cardiovascular diseases (CVDs). Many research projects and the resulting meta-analyses have reported controversial results for the use of hs-CRP, especially in the risk assessment of CVDs. However, since these analyses used different assays to detect hs-CRP, it is important to assess the current level of assay harmonization. Methods: This paper analyzes data from 17 external quality assessment (EQA) surveys for hs-CRP conducted worldwide between 2018 and 2023. Each EQA survey consisted of two blinded samples. In 2020 the sample material changed from pooled serum to single-donor samples. The aim was to assess the current status of assay harmonization by a manufacturer-based approach, taking into consideration the clinical decision limits for hs-CRP risk-stratification of CVDs as well as the scatter of results. Results: Our analyses show that harmonization has increased in recent years from median differences of up to 50 % to below 20 %, with one exception that showed an increasing bias throughout the observed period. After changing sample materials from pools to single-donor samples, the coefficient of variation decreased to below 10 % with one exception. Nevertheless, even these differences in the clinical setting could lead to disparate classification of patients depending on the assay used. Conclusion: While there was a positive trend towards harmonization, it is advised that patients be monitored when data from different assays are aggregated into one meta-analysis. Furthermore, assays are currently traceable to different international standard preparations, which might have a negative impact on future harmonization.